Effectiveness of the Implementation of the Minister of Education, Culture, Directorate, and Technology Regulation Number 46 of 2023 in Preventing Bullying and Strengthening Gender Equality - Muhammad Elmy; Bunyamin Maftuh; Mariatul Kiptiah; Kama Abdul Hakam (Universitas Negeri Malang, 2025)
This study aims to analyze the implementation of anti-bullying and gender equality regulations and their contribution to the internalization of character education values. This study used a descriptive quantitative method supported by qualitative data, using survey instruments and literature reviews. Data are analyzed using the Mazmanian and Sabatier policy implementation framework, ambiguity-conflict theory, and a character education framework. The results of the study indicate that anti-bullying and gender equality regulations have a clear legal basis, but the effectiveness of their implementation varies across schools. The prevalence of bullying remains high, especially in verbal forms at 48.1 percent and relational at 32.7 percent, and gender bias persists. The implementation of anti-bullying policies is experimental, while gender equality tends to be a symbolic implementation. The contribution of regulations is more on the aspects of moral knowing and partly moral feeling, but has not yet touched on moral action. Strengthening teacher capacity is needed through gender bias training, integration of indicators of School-Related Gender-Based Violence and Gender Equality, Disability, and Social Inclusion in national monitoring, and enrichment of practice-based character education.